AUGMENTED REALITY DALAM PEMBELAJARAN IPA BAGI SISWA SD - Bintoro Setyawan; nFn Rufii; Ach. Noor Fatirul (Balai Besar Guru Penggerak Jawa Timur, 2019)
Today's technological development is progressing, and is growing rapidly. This development certainly has an influence on various sectors of human life, one of which is the education sector. The latest rapid technological developments are the increasingly frequent use of devices, especially smartphone use in everyday life, including in the field of education. This opens up huge opportunities in utilizing application technology on smartphones to be developed into an application-based learning media. One of them is by utilizing Augmented Reality technology on android applications in science learning media for elementary school students in class VI so that students are motivated in learning and easier to understand the material being studied. For this reason, a learning media based on Augmented Reality (AR) was developed with the application of Unity science subjects. The material recognizes planets in the solar system for grade VI elementary school students, while seeing the quality of learning media produced in terms of validity, attractiveness and practicality. This research uses the development research model Borg and Gall, with several stages of development, namely: (1) data collection; (2) planning; (3) development; and (4) validation and trial. The results of the development research in the form of AR learning media showed very good and feasible results used as learning media, both in class and independently according to the results of learning design expert validation, media experts and teacher validation as material experts Student responses to the use of this media in learning were very good. Students are passionate about learning and arouse students' curiosity. AbstrakPerkembangan teknologi sekarang ini semakin maju, dan tumbuh dengan pesat. Perkembangan ini tentu saja membawa pengaruh pada berbagai sektor kehidupan manusia, salah satunya adalah sektor pendidikan. Perkembangan teknologi terkini yang pesat adalah semakin seringnya penggunaan gawai, khususnya penggunaan smartphone dalam kehidupan sehari-hari, termasuk di bidang pendidikan. Hal ini membuka peluang besar dalam memanfaatkan teknologi aplikasi pada smartphone untuk dikembangkan menjadi media pembelajaran berbasis aplikasi. Salahsatunya adalah dengan memanfaatkan teknologi Augmented Reality pada aplikasi android dalam media pembelajaran IPA bagi siswa sekolah dasar (SD) kelas VI agar siswa termotivasi dalam belajar dan lebih mudah untuk memahami materi yang dipelajari. Untuk itu dikembangkan media pembelajaran berbasis Augmented Reality (AR) dengan aplikasi Unity mata pelajaran IPA materi mengenal planet-planet di tata surya untuk siswa kelas VI SD, sekaligus melihat kualitas media pembelajaran yang dihasilkan ditinjau dari aspek validitas, kemenarikan, dan kepraktisan. Penelitan ini menggunakan model penelitian pengembangan Borg and Gall, dengan beberapa tahapan pengembangannya, yaitu: (1) pengumpulan data; (2) perencanaan; (3) pengembangan; dan (4) validasi dan uji coba. Hasil penelitian pengembangan berupa media pembelajaran AR menunjukkan hasil sangat baik dan layak digunakan sebagai media pembelajaran, baik di kelas maupun secara mandiri menurut hasil validasi ahli desain pembelajaran, ahli media dan validasi guru sebagai ahli materi Respon siswa terhadap penggunaan media ini dalam pembelajaran sangat baik. Siswa bersemangat dalam mengikuti pembelajaran dan membangkitkan rasa ingin tahu siswa.